Examine The Role Of Management Ownership In Unlocking Firm Value - Aprih Santoso; Tuti Dharmawati; Bastanta Prawira Tarigan; Pandu Adi Cakranegara; Irsyad Kamal (ITB AAS INDONESIA, 2023)
The purpose of this research is to analyze the effect of profitability and liquidity on firm value by moderating management ownership. The data were obtained from the financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the years 2018 – 2020. By using purposive sampling, 27 companies were selected as research samples. The data was processed by multiple regression analysis using the IBM SPSS Statistic 25 application. The results showed that profitability had a positive and significant effect on firm value, but liquidity had no effect on firm value. The results of the moderating variable test show that management ownership does not moderate the effect of profitability and liquidity on firm value. Keywords: ownership, liquidity, firm value, profitability